The effects of spin-orbit coupling on optical properties of monolayer $$\text {MoS}_{2}$$ MoS 2 due to mechanical strains - H. Rezania; M. Abdi; B. Astinchap; E. Nourian (Scientific Reports, 2023)
Abstract We have studied the optical conductivity of a quasi two-dimensional $$\text {MoS}_{2}$$ MoS 2 in the presence of external magnetic field and spin-orbit coupling. Specially, we address the frequency dependence of optical conductivity due to spin-orbit interaction. Using linear response theory the behavior of optical conductivity has been obtained within Green’s function method. We have also considered the effects of uniaxial and biaxial in-plane strain on the optical absorption of $$\text {MoS}_{2}$$ MoS 2 layer. In the absence of external magnetic field with negative uniaxial strain parameter, optical conductivity includes Drude weight at zero frequency limit while Drude weight vanishes for $$\text {MoS}_{2}$$ MoS 2 layer under positive uniaxial strain. Our results show that the increase of uniaxial positive strain parameter causes to move the position peak to the higher frequencies. In contrast to uniaxial strain case, the Drude weight in optical conductivity appears at positive biaxial strain value 0.15. Also we have studied the effects of magnetic field, electron doping, hole doping in the presence of spin-orbit coupling on frequency dependence of optical conductivity of $$\text {MoS}_{2}$$ MoS 2 in details. The magnetic field dependence of optical absorption shows a monotonic decreasing behavior for each value of temperature in the absence of strain parameter.